ChemInform Abstract: Copper‐Catalyzed Aerobic C—C Bond Cleavage of Lactols with N‐Hydroxy Phthalimide for Synthesis of Lactones. Issue 49 (December 2015) - Tnay, Ya Lin; Chiba, Shunsuke
Abstract: α, β‐Unsaturated lactones are obtained from various lactols through an unstrained C—Me bond cleavage as well as α, β‐unsaturation.